Assessment of Anti-TNF-α Activities in Keratinocytes Expressing Inducible TNF- α: A Novel Tool for Anti-TNF-α Drug Screening. - Sutthirat Udommethaporn; Tewin Tencomnao; Eileen M McGowan; Viroj Boonyaratanakornkit (PLoS ONE, 2016)
Tumor necrosis factor alpha (TNF-α) is a pro-inflammatory cytokine important in normal and pathological biological processes. Newly synthesized pro-TNF-α is expressed on the plasma membrane and cleaved to release soluble TNF-α protein: both are biologically active. Secreted TNF-α signals through TNF receptors and the membrane-bound TNF-α acts by cell contact-dependent signaling. Anti-TNF-α antibodies have been used effectively for treatment of chronic inflammation, however with adverse side effects. Thus, there is a need for new anti-TNF-α small molecule compounds. Anti-TNF-α activity assays involve treatment of keratinocytes with exogenous TNF-α before or after anti-TNF-α incubation. However, this model fails to address the dual signaling of TNF-α. Here we describe a Doxycycline (Dox)-inducible TNF-α (HaCaT-TNF-α) expression system in keratinocytes. Using this in-vitro model, we show cell inhibition and induced expression of pro-inflammatory cytokines and markers, including IL-1β, IL-6, IL-8, NF-κB1, and KRT-16, similar to cells treated with exogenous TNF-α. Sufficient secreted TNF-α produced also activated IL-1β and IL-8 expression in wt HaCaT cells. Importantly, stimulated expression of IL-1β and IL-8 in HaCaT-TNF-α were blocked by Quercetin, a flavanol shown to possess anti-TNF-α activities. This novel in vitro cell model provides an efficient tool to investigate the dual signaling of TNF-α. Importantly, this model provides an effective, fast, and simple screening for compounds with anti-TNF-α activities for chronic inflammatory disease therapies.